2011
DOI: 10.1021/je200270t
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Plant Biomass Components. Heat Capacity, Combustion Energy, and Gasification Equilibria of Cellulose

Abstract: Heat capacities and enthalpies of formation were determined for the well-characterized samples of cellulose of different origins. The obtained experimental results allowed us to obtain the accurate values of thermodynamic properties for this material. It was demonstrated that the heat capacity and entropy of cellulose samples can be linearly related with their crystallinity index. The equilibria of the processes of cellulose gasification were considered. The adiabatic temperatures of the gasification and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 10 publications
7
57
0
Order By: Relevance
“…1, the heat capacity of the different biomasses varies from 1300 to 2000 J kg À1 K À1 in the temperature range 313-353 K. These values are in the range of values commonly found on biomass in literature. Very good agreement was found with previous measurements on cellulose [10].…”
Section: Heat Capacity Measurement On Biomassessupporting
confidence: 91%
See 2 more Smart Citations
“…1, the heat capacity of the different biomasses varies from 1300 to 2000 J kg À1 K À1 in the temperature range 313-353 K. These values are in the range of values commonly found on biomass in literature. Very good agreement was found with previous measurements on cellulose [10].…”
Section: Heat Capacity Measurement On Biomassessupporting
confidence: 91%
“…Experimental studies on heat capacity can be found in literature on biomass species of interest for current industrial applications: woody species [5,6], together with cellulose, which is the main constituent of biomass and the main product used for pulp applications [7][8][9][10][11] or agricultural biomass for food applications, such as peanut [12], cassava, yam, plantain [13] or cumin seed [14]. To our knowledge, agricultural by-products were considered only by Mothée and De Miranda [15] with measurements on coconut fibre and bagasse and there are no available heat capacity data on energy crops or wood from Short Rotation Forestry (SRF) and Short Rotation Coppice (SRC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is likely that many of the samples of cellulose Ib used in these studies contained some cellulose Ia [4,79]. [91], and by Blokhin et al [92] lead, respectively, to D c H Ã w = À17337 JÁg À1 , D c H Ã w = À17458 JÁg À1 , and D c H Ã w = À17165 JÁg À1 for cellulose I(cr). The earlier, very carefully done measurements of Jessup and Prosen [83] and Colbert et al [87] did not include a measurement of CI but the samples that they used probably had high CI values.…”
Section: Mid T Fitsmentioning
confidence: 99%
“…Here, the uncertainty is equal to two estimated standard deviations of the mean. The value of D c H Ã w = À17165 JÁg À 1 from Blokhin et al [92] is an outlier and was not used in calculating the average. From our study, we have D c H Ã w = À(16048 ± 40) JÁg À1 for cellulose I(cr) (see table 8) that pertains to T = 298.15 K and w H 2 O = 0.073.…”
Section: Mid T Fitsmentioning
confidence: 99%